NOMOFOBIA: o excesso de informação e os relacionamentos digitais - SENADOR, ANDRÉ (2016)
The evolution of digital communication technologies is promoting a revolution in behaviors and changing deeply the relationships between people. The attraction caused by smartphones with its innovations and technologies, as well as the fascination exerted by social media are changing social relations and leading individuals who are enchanted by these devices to an excessive use. In this scenario of constant transformation of digital communication technologies, people spend most of their time and attention on browsing the Internet, posting, liking posts and relating to others through social media. These devices have started to be a part of people’s everyday lives in a way and with such intensity that it’s leading individuals to become dependent on its use and resources, and also presenting signs, when not being able to access it, of “nomophobia”, the new illness of the digital era. The term, created from the expression “no mobile” has become the term responsible for designating the discomfort caused by disconnection or absence of digital communication. This dissertation, through theoretical studies, presents a panorama of the development of digital communication technologies and seeks to analyze, through bibliographical review, the effects on the users whose attraction to these technologies are changing their behaviors and relationships. This text also shows how researchers in the field of health and psychology are identifying and interpreting the effects of nomophobia. This is a reflection to examine this subject that deserves more and more attention as well as to help understand its unfolding and effects on individuals in this new digital universe.